Generation and Export of Red Blood Cell ATP in Health and Disease - McMahon, Timothy J.; Darrow, Cole C.; Hoehn, Brooke A.; Zhu, Hongmei (Frontiers in Physiology, 2021)
Metabolic homeostasis in animals depends critically on evolved mechanisms by which red blood cell hemoglobin senses oxygen (O2) need and responds accordingly. The entwined regulation of ATP production and antioxidant systems within the RBC also exploits Hb-based O2-sensitivity to respond to various physiologic and pathophysiologic stresses. O2 offloading, for example, promotes glycolysis in order to generate both 2,3-DPG (a negative allosteric effector of Hb O2 binding) and ATP. Alternatively, generation of the NADPH critical for reducing systems is favored under the oxidizing conditions of O2 abundance. Dynamic control of ATP not only ensures the functional activity of ion pumps and cellular flexibility, but also contributes to the availability of vasoregulatory ATP that can be exported when necessary, for example in hypoxia or upon RBC deformation in microvessels. RBC ATP export in response to hypoxia or deformation dilates blood vessels in order to promote efficient O2 delivery. The ability of RBCs to adapt to the metabolic environment via differential control of these metabolites is impaired in the face of enzymopathies (pyruvate kinase deficiency; glucose-6-phosphate dehydrogenase (G6PD) deficiency), blood banking, diabetes mellitus, COVID-19 or sepsis, and sickle cell disease. The emerging availability of therapies capable of augmenting RBC ATP, including newly established uses of allosteric effectors and metabolite-specific additive solutions for RBC transfusates, raises the prospect of clinical interventions to optimize or correct RBC function via these metabolite delivery mechanisms.